Foseco ferrous foundryman's handbook - Brown, John R. (Oxford [England] ; Boston : Butterworth Heinemann, 2000)
The Foseco Ferrous Foundryman's Handbook is a practical reference book for all those concerned with making castings in any of the commonly used alloys, by any of the usual moulding methods. International SI units are used throughout, but in almost all cases conversions to the more familiar Metric and Imperial units are given. Wherever possible, Casting Alloy Specifications include equivalent specifications for several countries as well as international specifications. Individual chapters cover the casting of light alloys, copper-based alloys, all types of cast-iron and steel. For each group of alloys, specifications and typical applications are described, together with details of melting practice, metal treatment and casting practice. Sand moulding materials, including green sand and chemically bonded sands are also included.
Tables and general data; Sands and sand bonding systems; Coatings for moulds and cores; Light alloy castings; Copper and copper alloy castings; Iron castings; Die-castings; Steel castings; Feeding of castings; Computer modelling of solidification of castings, the SOLSTAR system; Filtration of castings; Principal Foseco products.
Includes index.
Keywords: Founding -- Handbooks, manuals, etc; Iron-founding -- Handbooks, manuals, etc; Cast-iron -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc